Determination of 2-Keto-L-gulonic Acid in Fermented Broth by Flow Injection Chemiluminescence Using Potassium Permanganate-Rhodamine B System - Lu1, Xinli; Feng2, Jing; Zhang3, Jujuan; Chen1, Suliang; Zhang1, Yuqi; Zhao1, Hongru (Asian Journal of Chemistry, 2013)
In this paper, a flow injection-chemiluminescence (FI-CL) was presented for the determination of 2-keto-L-gulonic acid in fermented broth. This method was based on enhance effect of 2-keto-L-gulonic acid on the chemiluminescence reaction between rhodamine B and potassium permanganate in acid medium. The optimized experimental conditions were evaluated. Under optimum conditions, calibration curve over the range of 0.2-60 mg L-1 was obtained. The detection limit of this method was 0.04 mg L-1. The relative standard deviation was 3.7 % for 2.0 mg L-1 2-keto-L-gulonic acid. The method validation has been compared versus HPLC method for determination of 2-keto-L-gulonic acid in fermented broth.